Electronic, optical, and transport properties of RbYbX3 (X = Cl, Br) for solar cells and renewable energy: a quantum DFT study. (3rd June 2021) - Mahmood, Q; Hedhili, F; Al-Shomar, S; Chebaaneef, S; Al-Muhimeed, Tahani I; AlObaid, Abeer A; Mera, Abeer; Alamri, Osama Abdulaziz
Abstract: The electronic, optical, and thermoelectric properties of RbYbX3 (X = Cl, Br) are investigated with density functional theory based Modified Becke and Johnson (mBJ) potential which is executed in Wien2K code. The tolerance factors (0.96, 0.98) and formation energies favor their structural and thermodynamic stabilities. The direct bandgaps of 1.42 eV and 1.30 eV for RbYbCl3, and RbYbBr3 address the visible region of spectrum for solar cells. The optical properties are explored comprehensively in terms of dielectric constants, refractive index, absorption coefficient, and reflection. The absorption bands of light are in the visible region, and light is plane-polarized. Furthermore, the thermoelectric properties are analyzed in terms of thermal and electrical conductivities, Seebeck coefficient, and figure of merit. The room temperature ZT turns out to be 0.78 for RbYbCl3 and 0.75 for RbYbBr3 . The maximum absorption in the visible region and high ZT make them excellent materials for renewable energy applications.